On warmers as the ionizing source in active galactic nuclei - Fernandes Junior, Roberto Cid (1992)
The aim of this paper is to study in detail the Terlevich & Melnick starburst-warmers scenario for type 2 Seyferts and LINERs, which postulates a young cluster containing stars with temperatures about 150 000 K as the heating source in these objects. A numerical code was developed to compute the total spectrum of a star cluster given its age and initial mass function. The ionizing spectra so obtained were used in the photoionization code AANGABA to calculate the nebular ernission-line spectra for a grid of cloud parameters covering different densities (and gradients), ionization parameters and metallicities. The evolution of the system was followed on classical diagnostic diagrams and a very good agreement with Terlevich & Melnick's results was found. We conclude that warmers can indeed be the ionizing source in many narrow-line AGN, although the coverage of AGN areas on diagnostic diagrams is not complete. We find the warmers model successful within a metallicity range between ~~0.5 and 2Z̛. The upper limit is set by the strong cloud cooling by forbidden lines. On the other hand, at Z<~0.5 Z̛ fewer stars would be thrown into 'warmer' phases due to the smaller mass-loss rates, and even if warmers occur the ernission-line spectrum would correspond to an H II galaxy rather than to an AGN. The chernical pollution of the gas by the strongly processed stellar winds of massive stars is also studied. Our results suggest that the nitrogen overabundance of AGN frequently claimed in the literature arises quite naturally in this scenario.